BUSANA MUSLIM : MENAKAR AKAR PENENTU KEPUTUSAN PEMBELIANNYA - Astuti, Selvy Indah Purwaning; Widowati, Sri Yuni; Santoso, Aprih (STAI Darul Qalam Tangerang, 2023)
This research was motivated by sales of Pands Muslim Department Store Semarang which never reached the target from 2016-2020. This study aims to analyze the effect of price, product quality and promotion on purchasing decisions at Pands Muslim Department Store Semarang. The population in this study were consumers who visited Pands Muslim Department Store Semarang. The sample used in this study were 96 respondents, using purposive sampling method. The data testing technique used includes the validity test with factor analysis, reliability test, classical assumption test, multiple linear regression analysis and the significance test of the coefficient of determination to prove the truth of the hypothesis. The test results obtained multiple linear regression analysis Y = + 0.536 X1 + 0.258 X2 + 0.159 X3 + e. There is a positive and significant effect of the Price variable on the Purchase Decision. There is a positive and significant effect of the Product Quality variable on the Purchase Decision. There is a positive and significant effect of the Promotion variable on the Purchase Decision. The predictive ability of the variables of the effect of Price, Product Quality and Promotion on Purchase Decisions is 67.9% while 32.1% is explained by other variables